Distribution of macrozoobenthos in the mangrove forest of marine protected areas (mpa) pariaman of west sumatra - Victor Simanungkalit; Afrizal Tanjung; Aras Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted on June 2013 in mangrove forest of Marine Protected Areas (MPA), Pariaman city West Sumatra Province. The method of this research was survey method, which primary data were gotten on research area. This study aimed to find out of macrozoobenthos distribution in mangrove forest of Marine Protected Areas (MPA) Pariaman of West Sumatra. Macrozoobenthos sampling was carried out on sub-plot measuring 1m x 1m, which plot measuring 5m x 5m, as many as 5 plot where as sediment samples were taken at each station.Macrozoobenthos species were found in this area, those are Cerithidea anticipata, Neritodryas dubia, Neptunea decemcostata, Ellobium aurisjudae, Littoraria sp, Pitar manillae, Tapes literata, Geloina coaxans and Uca coarctata. Morisita distribution index of macrozoobenthos on three stations around 1.0469 to 1.0252. Morisita distribution index on every station are more than 1 (> 1), it means that distribution characteristic from into groups.Keywords: Pariaman, Macrozoobenthos, Distribution